The timelines for the price and reimbursement authorization in Italy 2018–2020 - Gallo, Valentina; Alessi, Eva; Montilla, Simona; Altamura, Gianluca; Traversa, Giuseppe; Trotta, Francesco (Frontiers in Medicine, 2022)
The aims of this investigation were to guarantee the principles of transparency in the public administration; to inform the citizens about the time to patient access to reimbursed medicines; to assess for the first time in the period 2018-2020 the duration of the Price and Reimbursement process; to evaluate whether and how the SARS-CoV-2 pandemic affected the P&R activity. The study analysed the timelines of pricing and reimbursement procedures submitted in Italy by the pharmaceutical marketing authorisation holder from 2018 to 2020. The analysis was run through a AIFA web based platform, that collects data about the P&R procedures, for each step of the Italian P&R procedure, including dates of the Technical Scientific Committee and P&R Committee meetings from January 2018 to December 2020. On this basis, four indicators have been developed relating to the completion time of each stage of the P&R negotiation process and were defined in terms of days. In this regard, descriptive analysis, graphical boxplots and survival curves were carried out, studying these indicators in relation to typology of pharmaceutical procedures. In the period 2018-2020, 57,1% of the 2.445 procedures entered was represented by the Off-patent pharmaceuticals procedures. In 2020, the overall process was completed in 129,8 average days (95% CI: [122,3-137,2]) and 108 median value for Off-patent pharmaceutical procedures, while it was 283,1 average days (95% CI: [267,8-298,5]) and 284 median value for In-patent pharmaceutical procedures. Over time, the trend of the entire duration of the P&R process tends to decrease. In terms of estimated timing for the conclusion of each stage of the P&R negotiation process, the difference between Off-patent and In-patent pharmaceuticals procedures was statistically significant by the Log-Rank test. This is the first study to examine the time of the P&R process in Italy, from MAH submission to the publication in Official Journal of the final decision pharmaceuticals procedures in a time span of three years during the first year of the Covid-19 pandemic. Compared to the European average times, in Italy, the time necessary for evaluation, authorization for reimbursement and definition of the price of a medicine can be considered satisfactory.